1996
DOI: 10.1152/ajprenal.1996.271.4.f831
|View full text |Cite
|
Sign up to set email alerts
|

Role of apoptosis in development of the ascending thin limb of the loop of Henle in rat kidney

Abstract: At birth, the rat renal papilla has the structural composition of the mature inner stripe of the outer medulla. All loops of Henle have the configuration of short loops, and there are no ascending thin limbs. This study examines the role of apoptosis in the differentiation of the loop of Henle and the development of the ascending thin limb in the rat kidney. Kidneys of 20-day-old fetuses and 1-, 3-, 5-, 7-, 14-, and 21-day-old pups were preserved for immunohistochemistry and electron microscopy. Using a preemb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
48
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(56 citation statements)
references
References 0 publications
7
48
0
1
Order By: Relevance
“…3O arrow). This physiological apoptosis plays an essential role in the generation of the thin ascending limb of the mature HL, which first appears just after birth in rat kidneys (Kim et al, 1996). In Brn1 -/-kidneys lacking immature loops (Fig.…”
Section: Elongation Of Hls Was Severely Retarded In Homozygous Brn1-mmentioning
confidence: 94%
“…3O arrow). This physiological apoptosis plays an essential role in the generation of the thin ascending limb of the mature HL, which first appears just after birth in rat kidneys (Kim et al, 1996). In Brn1 -/-kidneys lacking immature loops (Fig.…”
Section: Elongation Of Hls Was Severely Retarded In Homozygous Brn1-mmentioning
confidence: 94%
“…Consistent with this notion, the renal medulla separates into an outer and inner zone only after birth (3). This separation is realized by differentiation of loops of Henle leading to formation of thin limbs via coordinated cell proliferation and selective apoptosis (4,8). Local hypertonicity and cell shrinkage may be important factors controlling apoptosis in the developing kidney, but their role in the developmental differentiation of the kidney medulla is presently unexplored.…”
mentioning
confidence: 99%
“…Kim et al (4) reported that the cuboidal epithelium of the TAL of the renal papilla is gradually transformed into the ATL during the first 2 weeks of life. However, despite this study, little is currently known about a trigger for this structural change.…”
Section: Discussionmentioning
confidence: 99%